Surgical crown lengthening for enhanced esthetics and function in full mouth rehabilitation: a case report - Dias, Clarence; Lawande, Sandeep; Samuel, James (Medico Research Chronicles, 2020)
Full mouth rehabilitation is one of the most challenging treatment procedures in dentistry because it requires comprehensive diagnosis and systematic treatment planning to reach the best outcome that optimizes function, health and aesthetics. Crown lengthening procedures have become an integral component of the aesthetic armamentarium. To utilize crown lengthening, understanding the concept of biologic width is of particular importance. Surgical crown lengthening plays a crucial role in creating a healthy and harmonious relationship of the gingiva and bone levels to gain sound tooth structure, which can be restored in cases of short clinical crowns. This article describes surgical crown lengthening for full mouth rehabilitation in a 26-year-old female patient with inadequate clinical crown height.